2008
DOI: 10.1103/physrevb.78.134422
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a dynamic phase transition in[Co/Pt]3magnetic multilayers

Abstract: A dynamic phase transition (DPT) with respect to the period P of an applied alternating magnetic field has been observed previously in numerical simulations of magnetic systems. However, experimental evidence for this DPT has thus far been limited to qualitative observations of hysteresis loop collapse in studies of hysteresis loop area scaling. Here, we present significantly stronger evidence for the experimental observation of this DPT, in a [Co(4Å)/Pt(7Å)] 3 -multilayer system with strong perpendicular anis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 37 publications
9
85
0
Order By: Relevance
“…As an example, a DPT occurring in high frequency region is represented by Jiang et al [3] using the surface magneto-optical Kerr-effect technique for epitaxially grown ultrathin Co films on a Cu(001) surface. For a [Co(4A o )/Pt(7A o )] multilayer system with strong perpendicular anisotropy, an example of DPT is shown by Robb et al [4]. In this study, they found that the experimental nonequilibrium phase diagrams are found to strongly resemble the dynamic behavior calculated from simulations of a kinetic Ising model.…”
Section: Introductionsupporting
confidence: 62%
“…As an example, a DPT occurring in high frequency region is represented by Jiang et al [3] using the surface magneto-optical Kerr-effect technique for epitaxially grown ultrathin Co films on a Cu(001) surface. For a [Co(4A o )/Pt(7A o )] multilayer system with strong perpendicular anisotropy, an example of DPT is shown by Robb et al [4]. In this study, they found that the experimental nonequilibrium phase diagrams are found to strongly resemble the dynamic behavior calculated from simulations of a kinetic Ising model.…”
Section: Introductionsupporting
confidence: 62%
“…One of the key results is the existence of a so-called dynamical phase transition, where the cycle-averaged magnetization becomes non-zero in a singular fashion. This has recently been supported by experimental evidence in the dynamics of thin ferromagnetic films [34].…”
mentioning
confidence: 55%
“…On the experimental picture, it can be said that a great many of experimental studies have been devoted to DPTs and hysteresis behaviors of Co films on a Cu (001) surface [32], [Co(4A o )/Pt(7A o )] multi-layer system with strong perpendicular anisotropy [33], thin polycrystalline Ni 80 Fe 20 films [34], ultrathin ferromagnetic Fe/Au(001) films [35], epitaxial Fe/GaAs(001) thin films [36], epitaxial single ferromagnetic fcc NiFe(001), fcc Co(001), and fcc NiFe/Cu/Co(001) layers [37], Fe 0.42 Zn 0.58 F 2 [38], finemet thin films [39], and epitaxial Fe/GaAs(001) and Fe/InAs(001) ultrathin films [40]. After some detailed experimental investigations, it has been observed that experimental non-equilibrium dynamics of considered real magnetic systems strongly resemble the dynamic behav-ior predicted from theoretical calculations of a kinetic Ising model.…”
Section: Introductionmentioning
confidence: 99%